Survival, metabolic activity, and ultrastructural damages of Antarctic black fungus in perchlorates media - Cassaro, Alessia; Pacelli, Claudia; Onofri, Silvano (Frontiers in Microbiology, 2022)
Evidence from recent Mars landers identified the presence of perchlorates salts at 1 wt % in regolith (Hecht et al., 2009) and their widespread distribution on the Martian surface (Davila et al., 2013) that has been hypothesized as a critical chemical hazard for putative life forms. However, the hypersaline environment may also potentially preserve life and its biomolecules over geological timescales. The high concentration of natural perchlorates is scarcely reported on Earth. The presence of perchlorates in soil and ice has been recorded in some extreme environments including the McMurdo Dry Valleys in Antarctica (Kounaves et al., 2010), one of the best terrestrial analogues for Mars (Friedmann, 1982; Onofri et al., 2004). In the frame of “Life in space” Italian astrobiology project, the polyextremophilic black fungus Cryomyces antarcticus, a eukaryotic test organism isolated from the Antarctic cryptoendolithic communities, has been tested for its resistance, when grown on different hypersaline substrata. In addition, C. antarcticus was grown on Martian relevant perchlorate medium (0.4 wt% of Mg(ClO4)2 and 0.6 wt% of Ca(ClO4)2) to investigate the possibility for the fungus to survive in Martian environment. Here, the results indicate a good survivability and metabolic activity recovery of the black fungus when grown on four Martian relevant perchlorates. A low percentage of damaged cellular membranes have been found, confirming the ultrastructural investigation.